Thailand : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation discusses Thailand's robust policy framework and ample buffers continue to underpin its resilience to external headwinds. The authorities have taken measures to strengthen medium-term fiscal management and financial stability. With respect to the outlook, growth is projected to slow down to about 3 percent in 2019-20 reflecting external and domestic headwinds. On the external side, the projected slowdown in global demand and uncertainty about trade tensions are expected to weigh on exports throughout 2019. Policies should aim at boosting growth, while promoting domestic and external rebalancing and making growth more inclusive. The IMF staff recommends a front-loaded fiscal impulse in FY 2020. Thailand should use available fiscal space judiciously to spur domestic demand and support potential output. Implementation of macro-critical public infrastructure projects would also crowd in private investment. The report also highlights that structural reforms aimed at improving the implementation of public investment, strengthen social safety nets, and raise productivity in an increasingly digital economy, would boost growth and enhance its inclusiveness.